Analysis of Socio-Economic Aspects of MSMEs Processing Salak Taman Ambudi Makmur 2 in the Perspective of Business Feasibility Studies - Vifin Nadzary AL Awaly; Abdur Rohman (Demagogi: Journal of Social Sciences, Economics and Education, 2025)
Arrangement and Development of salak processing factories in Kramat Village, Bangkalan in fostering industrial development and management of salak fruit as well as the smooth development of a community agricultural product. And the growth of the number of companies engaged in trade in Kramat Village is always increasing, especially those on a large and micro scale. The purpose of this study is to assess from the socio-economic aspects of the community the existence of salak processing factories in order to provide identification of various alternatively, there are positive values and negative impacts internally and externally, related to the traditional market and the socio-economic life of the community. The type in this study also uses qualitative descriptive where a research intends to understand the phenomena experienced by the research subject, such as behavior, perception, motivation, action, and other things holistically and by describing in the form of words and language in a special context that and by utilizing various natural methods by using respondent data sources as sampling, in this case with the survey method. From the results and discussion by considering the socio-economic aspects and conditions in Kramat Village, Bangkalan, namely comparing positive and negative impacts on the construction of salak processing factories, it can be concluded that the construction project of salak processing factories in Bangkalan Kramat Village is feasible. The suggestion proposed is that the management must be must be professional and there is healthy competition.